2016
DOI: 10.1371/journal.pone.0162755
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of mGluR1a and mGluR5 Activation on Nucleus Accumbens Medium Spiny Neuron Dendritic Spine Density

Abstract: The group I metabotropic glutamate receptors (mGluR1a and mGluR5) are important modulators of neuronal structure and function. Although these receptors share common signaling pathways, they are capable of having distinct effects on cellular plasticity. We investigated the individual effects of mGluR1a or mGluR5 activation on dendritic spine density in medium spiny neurons in the nucleus accumbens (NAc), which has become relevant with the potential use of group I mGluR based therapeutics in the treatment of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,423 publications
(26 citation statements)
references
References 37 publications
(53 reference statements)
4
22
0
Order By: Relevance
“…The effects of estradiol on plasticity in the NAc of OVX females are mediated by mGluR5 in the NAcC, but not in the shell subdivision; MPEP treatment alone has no effect in either subdivision (Peterson et al, 2014). In contrast, treatment of OVX females with CDPPB (in the absence of estradiol) induces plasticity in both regions (Gross et al, 2016). It is perhaps not surprising, then, that widespread activation of mGluR5 (via systemic CDPPB administration) did not mimic the effect of estradiol in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effects of estradiol on plasticity in the NAc of OVX females are mediated by mGluR5 in the NAcC, but not in the shell subdivision; MPEP treatment alone has no effect in either subdivision (Peterson et al, 2014). In contrast, treatment of OVX females with CDPPB (in the absence of estradiol) induces plasticity in both regions (Gross et al, 2016). It is perhaps not surprising, then, that widespread activation of mGluR5 (via systemic CDPPB administration) did not mimic the effect of estradiol in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The mGluR5-positive allosteric modulator 3-cyano- N -(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB; 3235, Tocris) was dissolved in 10% Tween-80 (low CDPPB, 10 mg/ml/kg; high CDPPB, 25 mg/2 ml/kg) and injected i.p. The 10 mg/ml/kg dose of CDPPB mimics the effects of estradiol on dendritic spine density in the NAc in OVX females (Gross et al, 2016). Cocaine (cocaine hydrochloride; 0406-1520-53, Mallinckrodt, St. Louis, MO) was dissolved in sterile PBS (9.3 mg/ml) and infused i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that knocking down CAV‐1 protein levels reduced trafficking of full‐length ERα, and mediated coupling with mGluR1a, which activates excitatory actions of estradiol, including: intracellular calcium, PKC, MAPK, and ultimately CREB . In addition to the hypothalmus, the ER and mGluR interactions mediate estradiol suppression of GABAergic inhibition in female rats via an intracellular signaling pathway involving phospholipase C and inositol triphosphate, inhibition of internal free calcium in DRG cells, and striatal function …”
Section: Discussionmentioning
confidence: 98%
“…Initial experiments with cultured hippocampal neurons from males and females demonstrated that estradiol induces ERα trafficking to the membrane in association with caveolin (CAV) proteins . These observations have been confirmed in hypothalamic and striatal neurons and hypothalamic astrocytes and dorsal root ganglion cells from males and females . Knockdown of ARH caveolin‐1 (CAV‐1) prevented ERα trafficking to the membrane, but did not alter cytosolic levels of the receptor .…”
Section: Introductionmentioning
confidence: 93%
“…In male cultures, estradiol does not induce pCREB, while mGluR activation does. In addition, activation of mGluR5 mediates spine plasticity in male NAcC and NAcSh (Gross et al, 2016), suggesting that mGluRs possibly couple to membrane bound androgen receptor in males. The androgen receptor has indeed also been shown to migrate to the membrane (Tabori et al, 2005), using the same intracellular processes as estrogen receptors (Pedram et al, 2007).…”
Section: Discussionmentioning
confidence: 99%